The Effect of the Student Teams Achievement Divisions (STAD) Learning Model through Jeopardy Game Media on Students' Problem-Solving Abilities - Rasti Uliah; Umar Umar; Syahru Ramadhan; Ikhsan Maulana; Agus Setiawan (Journal of Mathematics Science and Computer Education, 2026)
This study aims to examine the effect of the Student Teams Achievement Division (STAD) learning model, integrated with Jeopardy game media, on students’ problem-solving abilities in Integrated Science and Social Studies (IPAS) at the elementary school level. This research employed a quasi-experimental design with a pretest-posttest control group. The research subjects were students of MIN Bima City. Data were collected using a problem-solving test as the main instrument. The data were analyzed using descriptive and inferential statistics to determine the significance of the differences between groups. The results showed that students taught using the STAD model through the Jeopardy game media achieved significantly higher problem-solving abilities compared to those taught using conventional methods. In conclusion, integrating the STAD learning model with the Jeopardy game media effectively improves students’ problem-solving abilities and can serve as an alternative strategy for IPAS learning at the elementary level.